Persepsi Guru Sekolah Dasar tentang Hakikat Pendidikan dan Ilmu Pendidikan Serta Relevansinya dengan Kurikulum Merdeka - Deva Maria Pangaribuan; Eva Betty Simanjuntak; Dinda Prati Dina Arsah; Enjel Anatasia Hutabarat; Fajra Lativa Asri; Sazkyla Nur Efendi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe elementary school teachers’ perceptions of the essence of education and educational science, as well as their relevance to the implementation of the Merdeka Curriculum. Education, as a process of developing students’ potential, requires teachers to understand the philosophical, theoretical, and practical foundations of educational science in order to implement the curriculum effectively. This research employed a qualitative descriptive method with data collected through interviews, questionnaires, and documentation studies involving elementary school teachers from several schools. The findings reveal that most teachers have a good understanding of the essence of education as an effort to shape character, develop competencies, and instill moral values. However, gaps remain in their comprehension of educational science as a scientific foundation that guides educational practices. The relevance to the Merdeka Curriculum is reflected in teachers’ efforts to emphasize student-centered learning, differentiation, and character strengthening in line with the Profil Pelajar Pancasila. In conclusion, teachers’ perceptions of the essence of education and educational science contribute significantly to the effective implementation of the Merdeka Curriculum, although strengthening teachers’ conceptual and pedagogical insights is still needed to ensure more comprehensive and applicable understanding.